Implementasi Kebijakan Dividen Di Koperasi Karyawan Tjiwi Kimia: Perspektif Keadilan dan Partisipasi Anggota - Oktaviani Putri Dita Arumsari; Aulia Ramadhani; Rizki Amalia Utami; Ig Jarot Febri Setyo Wibowo; Eli Siswanto (Master Manajemen, 2025)
This study to describe the mechanism for implementing dividend policies at the Koperasi Karyawan Tjiwi Kimia based on Law No. 25 of 1992. The focus of the research is the fair and transparent distribution of the Sisa Hasil Usaha (SHU) based on member participation. This study uses a descriptive qualitative method to depict the dividend policy implementation mechanism at the Koperasi Karyawan Tjiwi Kimia. The research subjects are it’s management, and data is obtained through interviews and documentation. Data validity is ensured through triangulation and member checks. The results show that the Koperasi Karyawan Tjiwi Kimia applies principles of open membership, democratic management, member economic participation, community concern, profit orientation, and socio-economic welfare. The Koperasi Karyawan Tjiwi Kimia’s functions include economic empowerment of members, provision of goods and services, skill development, and security control. The research finds that SHU is divided into several parts: 60% for members, with the remainder allocated for reserves, management/employees, social purposes, and education. Factors influencing dividend policies include financial performance, decisions from the Annual General Meeting or Rapat Anggota Tahunan (RAT), and capital reserve.